Discrimination against Citizens' Rights When the Entry of Foreign National Citizens Threatened By Emergency Public Activity Restrictions (PPKM) - Gunawan Nachrawi; Marjan Miharja; Rachmat Dwi Putranto; Jean Magtel Pah; Mayang Maharani Yahya Bayan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The entry of foreign national citizens (foreigners) into Indonesia when emergency public activity restrictions are enacted jeopardizes citizens' rights, including the freedom of movement within the country. The aim of this study is to ascertain whether there was prejudice against citizens when the emergency public cactivity restrictions (PPKM) was at stake regarding foreign national citizens' (foreigners') admittance into Indonesia. The descriptive method combined with a literature review was employed in this investigation (literature study). This legal study employs secondary primary law materials in the form of legislation containing discussions of legal topics and legal publications such as textbooks, legal dictionaries, legal journals, and other legal literature. The findings of this study reveal that when limits on community activities are enacted, the entry of foreign citizens (foreigners) into Indonesia becomes a productive contraption, as it may jeopardize the lives of Indonesian locals.